Determinants of Obesity Control Behavior in the Oil and Gas Industry: A Review Integrating the Theory of Planned Behavior with Occupational Health Factors - Puspita, Nabila Anggraeni; Roikhan, Muhammad Abdillah (Bunda Edu-Midwifery Journal (BEMJ), 2025)
The rising prevalence of obesity among the workforce poses a significant challenge, particularly within high-demand industrial sectors like oil and gas. While the Theory of Planned Behavior (TPB) provides a robust framework for understanding health intentions, its application often overlooks potent, context-specific occupational factors. This narrative review aims to synthesize literature on the determinants of obesity control among workers by integrating the core constructs of the TPB with critical findings from occupational health science. A literature search was conducted focusing on studies from 2015-2025 related to the TPB, workplace health, work stress, fatigue, and social culture, particularly in industrial settings. The review finds that while attitude, subjective norms, and perceived behavioral control are key predictors, their effects are significantly influenced by workplace realities. Specifically, work-related fatigue, often exacerbated by long hours or shift work, creates a gap between intention and behavior. High occupational stress can trigger automatic unhealthy eating patterns as a coping mechanism. Furthermore, the unique social culture within industrial workplaces provides powerful, immediate pressure that shapes choices through social identity and descriptive norms. As a synthesis of the reviewed evidence, this article presents an integrated conceptual framework that illustrates the complex interplay between these psychosocial and occupational determinants. This framework provides a more holistic understanding and can serve as a guide for future research and the development of more effective wellness interventions in demanding industrial environments.